2011
DOI: 10.18832/kp2011027
|View full text |Cite
|
Sign up to set email alerts
|

Influencing malt quality by exogenous ethylene application performed in the course of post-harvest ripening of barley grain.

Abstract: 1 Výzkumný ústav pivovarský a sladařský, a.s., Sladařský ústav Brno, Mostecká 7, 614 00 Brno / Research Institute of Brewing and Malting, PLC, Malting Institute Brno, Mostecká 7, 614 (2007)(2008)(2009), byly prováděny ve skleněných lahvích (3 800 ml) uzavřených pryžo-vou membránou. V těchto pokusech byl zkoušen vliv různé koncentrace ethylenu na kvalitativní ukazatele sladu. Vzhledem k malému objemu použitých nádob (2.000 ks obilek), však docházelo k rychlým změnám ve složení vzduchu, především k prudkému p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The germination curves also suggested that ethylene is the dominant hormone that determines the rate of germination of 'Puma' barley seed. Considering that ethylene is synthesised by germinating barley seeds (Locke et al 2000;Hartman et al 2011), the curves showed that supplementing ethylene synthesised by seeds (control) by exogenous ethylene treatment further reduces the number of seeds that germinates after 24 h and increases the number of seeds that germinates after 48 h. Moreover, inhibiting ethylene perception increased the number of seeds that germinated after 24 h. It could be concluded that ethylene treatment delays germination of 'Puma' barley and inhibiting its perception hastens germination.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The germination curves also suggested that ethylene is the dominant hormone that determines the rate of germination of 'Puma' barley seed. Considering that ethylene is synthesised by germinating barley seeds (Locke et al 2000;Hartman et al 2011), the curves showed that supplementing ethylene synthesised by seeds (control) by exogenous ethylene treatment further reduces the number of seeds that germinates after 24 h and increases the number of seeds that germinates after 48 h. Moreover, inhibiting ethylene perception increased the number of seeds that germinated after 24 h. It could be concluded that ethylene treatment delays germination of 'Puma' barley and inhibiting its perception hastens germination.…”
Section: Discussionmentioning
confidence: 98%
“…During germination, the barley seed produces GA (Palmer 2018) and ethylene (Locke et al 2000;Hartman et al 2011) which regulates embryo growth and enzyme synthesis. Since both ethylene and GA are produced by the germinating barley seed and their presence either in or around the seed affects germination, the separate roles of these hormones on barley seed germination are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation